BellBot - A Hotel Assistant System Using Mobile Robots. (15th January 2013) - López, Joaquín; Pérez, Diego; Zalama, Eduardo; Gómez-García-Bermejo, Jaime
There is a growing interest in applying intelligent technologies to assistant robots. These robots should have a number of characteristics such as autonomy, easy reconfiguration, robust perception systems and they should be oriented towards close interaction with humans. In this paper we present an automatic hotel assistant system based on a series of mobile platforms that interact with guests and service personnel to help them in different tasks. These tasks include bringing small items to customers, showing them different points of interest in the hotel, accompanying the guests to their rooms and providing them with general information. Each robot can also autonomously handle some daily scheduled tasks. Apart from user-initiated and scheduled tasks, the robots can also perform tasks based on events triggered by the building's automation system (BAS). The robots and the BAS are connected to a central server via a local area network. The system was developed with the Robotics Integrated Development Environment (RIDE) and was tested intensively in different environments.